Relationship between parental oral health literacy and children’s oral health status - Mohamad, Nasrul; Abu Bakar, Hariz; Ismail, Ahmad Faisal; Ardini, Yunita Dewi (2018)
Introduction: Oral Health Literacy (OHL) is the degree to which individuals have the capacity to obtain and process basic oral health information and services needed to make appropriate health decisions. Studies to evaluate the influence of OHL and its clinical outcomes however remains scarce. This research is conducted with the aim to assess the parental Oral Health Literacy (OHL) and its association with the oral health status of preschool children in Kuantan area. Materials and methods: Ethical approval is obtained prior to starting the study (IREC 766). A total of 200 sample of parent/child dyads that consented to participate are recruited from kindergartens around Kuantan. Inter- and intra-examiner calibration were performed prior to starting the clinical examination. Parental OHL level are assessed using REALD-99 tools and their demographic information were recorded. Clinical examination was performed by 2 calibrated examiner on the children to assess their oral health status using two parameters; dental caries experience (dmft) and oral hygiene status (visible plaque index). Results: Mean for dmft and VPI are 6.24 and 70.39%, respectively. Negative correlation is obtained between parental OHL and the oral health status of children indicating that when parental OHL level increases, the total dmft and VPI decreases (p<0.05). Lower dmft and VPI score were also observed among preschool children of parents in group with high parental OHL (p<0.05). Conclusion: There is significant association between parental OHL and children’s oral health status of preschool children in Kuantan, with higher parental OHL score associated with good children’s oral health.